Analysis of Regional Financial Performance through the Independence Ratio, Effectiveness Ratio, and Growth Ratio in the District South Bangka - Oktalina, Gayatria (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2020)
One of the positive effects of the implementation of regional autonomy is the proliferation of provinces or regencies/cities that is most common throughout Indonesia. One area resulting from the expansion is South Bangka Regency. As a new Regency that grew up in the era of regional autonomy, South Bangka Regency has a license to own its own area. The purpose of this research is to find out the Regional Government Financial Performance of South Bangka Regency. The data collection method used is documentation. While the method of analysis uses descriptive quantitative methods using financial ratios. The Financial Performance of South Bangka Regency Government in 2014-2018 when seen from the ratio of Regional Financial Independence is 7.10%. Regional Financial Effectiveness Ratio of 111.12% which means very effective. Regional Financial Ratio 40.00% is at medium level.